Tindak Lanjut Penuntasan Kasus Korupsi Mendiang Presiden Soeharto dalam Rangka Mewujudkan Cita-Cita Reformasi - Sri Handayani Retna Wardhani; Nita Ariyani; Paryadi (Fakultas Hukum Universitas Janabadra, 2022)
Abstract Follow-up to the Completion of the Corruption Case involving the late President Suharto has only managed to handle the Supersemar Foundation but has not touched 6 other foundations or been sued by the state to be held accountable for the management of state assets and funds which began during “Orde Baru” era. Meanwhile, many legal cases related to gross human rights violations have not been tried until today. This study aims to analyze the follow-up to the completion of the corruption case involving the late President Soeharto and the juridical steps that must be taken in solving the corruption case. The researcher uses a normative type of research using a legal approach and an analytical approach. effective steps related to accountability as well as allegations of misappropriation of state-owned funds and/or assets causing state losses related to the corruption case.